Assessing the Rain Estimate from the Feflectivity of Nha Be Radar - Thanh, Cong; Nhu Quy, Nguyen; Van Khiem, Mai (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1SDO - 10.25073/2588-1094/vnuees.4330, 2018)
Abstract: This study evaluates the estimated rainfall from Nha Be radar observation using different experimental formulas. The results show that in six estimation formulas used, the formulation of Joss' large-scale rainfall estimation and Marshall-Plamer's formulation can be used to estimate precipitation for the southwest monsoon with an error of approximately 5 mm/h and usually smaller than the observed value. The rainfall estimation formula by Nguyen Huong Dien is the optimum estimation for the 9 synoptic rainfall patterns: Intertropical Convergence Zone, Southwest monsoon associated with Intertropical Convergence Zone, low-pressure area, thunderstorm, disturbance in East winds, low-pressure area associated with Southwest monsoon, low-pressure troughs have a Northwestern-Southeasterly direction and other synoptic patterns with errors: 5mm/h, 9.5 mm/h, 14 mm/h, 7mm/h, 19 mm/h, 8 mm/h, 8.5 mm/h, 9.5 mm/h and 14.7 mm/h, respectively. Keywords :  Radar, rain estimate. References: [1] Nguyễn Hướng Điền, 2015. Công thức thực nghiệm tính toán cường độ mưa từ độ phản hồi radar cho khu vực Đông Nam Bộ. Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ, Tập 31, Số 3S tr.66 -70. [2] WMO/ASEAN Training Workshop on Weather Radar Data Quality and Standardization held in Bangkok, Thailand, from 5 to 13 February 2018 [3] Battan, L.J., 1973. Radar observation of the atmosphere. The University of Chicago Press, Chicago, 324 pp. [4] J. S. Marshall and W. McK. Palmer (1946), “The Distribution of Raindrop with Size”, Journal of Meteorology, 5, pp. 165-166. [5] J. Joss, Karin Schram, J. C. Thams and A. Waldvogel (1970), “On the Quantitative Determination of Precipitetion by a Radar”, Issue 63 of Wissenschaftliche Mitteilung. [6] D. Jones (1956), “Rainfall Drop Size-distribution and Radar Reflectivity”, Research Report No. 6.